An innovative educational media for reproductive health: The impact of the pillow t-shirt on knowledge among junior high school girl - Sari, Gita Nirmala; Ichwan, Erika Yulita; Aticeh; Munawarah, Raudhatul; Sukamti, Sri; Mulyana, Nana; Mulyati, Sri; Yamada, Eri (Journal of Health Technology Assessment in Midwifery, 2025)
Enhancing reproductive health knowledge among adolescents is crucial to prevent unwanted pregnancies. This study aims to develop and evaluate the effectiveness of the "Reproductive Health Pillow T-Shirt GIRL" educational media using the Research and Development (R&D) method. This interactive media was designed in collaboration with professional fashion designers and media experts. A quasi-experimental study with a control group was conducted involving 98 adolescent girls aged 13–15 years in junior high schools in Jakarta. The intervention group utilized the "Pillow T-Shirt," while the control group received lectures using audiovisual aids. Results demonstrated a significant increase in knowledge among the intervention group compared to the control group. This media shows promise as a standard educational tool for reproductive health in schools.